Case Report: Repeated Intralesional Injections of Autologous Mesenchymal Stem Cells Combined With Platelet-Rich Plasma for Superficial Digital Flexor Tendon Healing in a Show Jumping Horse - Melotti, Luca; Carolo, Anna; Elshazly, Noha; Boesso, Filippo; Da Dalt, Laura; Gabai, Gianfranco; Perazzi, Anna; Iacopetti, Ilaria; Patruno, Marco (Frontiers in Veterinary Science, 2022)
In the present case report a show jumping 10-year-old Sella Italiano gelding, presented with severe lameness, swelling and pain at palpation of the mid-metacarpal region of the left forelimb. Clinical and ultrasound examinations diagnosed a chronic tendonitis of the central region of the superficial digital flexor tendon (SDFT). The lesion was a recidive since it developed from a previous healed injury. The horse had to stop from competing and was unresponsive to gold-standard treatments as non-steroidal anti-inflammatory drugs (NSAIDs) and conservative management after six months of therapy. The animal was subjected to a repeated intralesional injection of autologous adipose-derived mesenchymal stem cells (AD-MSCs) combined with autologous platelet-rich plasma (PRP). The combined treatment was administered twice in a one-month interval. The healing process was assessed through clinical examination, ultrasound imaging and quantification of oxidative stress products and inflammatory mediators in blood plasma. After two weeks, a reduction of concentration of oxidative-derived products was observed, in concomitance with an increase of anti-inflammatory cytokines and pro-mitotic growth factors. These results were reflected clinically as the horse showed a reduction of lameness along with swelling and pain after 4 weeks. At the one-year follow-up, the horse showed no signs of lameness and swelling. The ultrasonographic examination highlighted a compact fiber alignment with a normal echogenic tendon as observed in the sound contralateral limb. Moreover, the horse went back to the previous level of competition. Our results suggest the positive synergic effects of a repeated intralesional injection of AD-MSCs and PRP for the treatment of a chronic tendonitis with long-term effects and an improvement for both equine quality of life and athletic performance.